The Effectiveness of Learning to Listen to YouTube-Based Fairy Tales in Learning Sundanese Language and Culture - Indriani, Rini Sri; Suchyadi, Yudhie; Budiana, Sandi; Martha, Layung Paramesti; Nurfauziyyah, Sifa (UNIVERSITAS PAKUAN, 2024)
Sundanese fairy tales are part of the Indonesian oral tradition and literature, which are told by word of mouth and therefore have the advantage of being conveyed in everyday language so that listeners will better understand what is being conveyed to them. However, on the other hand, the quality of the storyteller's understanding of the content, meaning and interpretation of fairy tales can be reduced because of their oral nature. Listeners of fairy tales as an important part of oral tradition also experience changes in orientation due to technology and generational shifts, including in Sundanese families. So, if this condition is left unchecked, it is not impossible that fairy tale oral literature will lose its supporters and eventually perish. Information technology, especially cellular communication technology, is an inseparable part of the society that supports this fairy tale literature. This rapid technological development, including tablet computers, can be used as an opportunity to make efforts to revitalize fairy tale culture in the next generation of supporters. This research has a background of students' lack of knowledge in listening to fairy tales in the Sundanese Language and Culture Learning course. Therefore, this research aims to examine students' ability to listen to fairy tales effectively on YouTube media in the Sundanese Language and Culture Learning course. This study uses a quantitative approach. The method used is an experimental method with a pre-test and post-test design. The data sources in the research were students who taught the Sundanese Language and Culture Learning course, totaling 68 students. The Technology Readiness Level states that the relevant facts and basic arguments are ready to support the need for this research. The hypothesis, initial support, RD design to be carried out have been explored, then the methodology, procedures and stages to be carried out have been explored. This research was designed with the adequacy and completeness of the data to be determined, with technical evaluation and prediction of results to be carried out. The results of the research can be concluded into several things: The ability to listen to PGSD students' stories before using YouTube media is not satisfactory. Because only 10.68% of the 68 students who had just understood the contents of the fairy tales had been listened to, therefore research was carried out using YouTube media in order to increase the value in learning to listen to fairy tales. After using YouTube media, students' ability to listen to fairy tales from 68 students who understood the contents of the fairy tales they had listened to was 44.82%. So the influence of YouTube media on the ability to listen to fairy tales of PGSD students on learning outcomes before and after using YouTube media can improve listening to fairy tales.